Quo Vadis Medical Healing Past Concepts and New Approaches - Elm, S.; Willich, Stefan N. (International Library of Ethics, Law, and the New Medicine, 2009)
Medical healing implies knowledge of the assumptions that underlie our understanding of "health," and, concomitantly, how we define well being and its opposites, illness and disease. Today, health, health care (business, wellness, recreation), and medicine (especially research-driven scientific medicine) have become separate entities with different institutions, budgets, marketing philosophies and "corporate cultures". Furthermore, healing is individual and subjective, yet at the same time also culturally determined. The present volume brings together papers on these topics in an unique interdisciplinary approach. The book provides an ethical framework for healthcare from a political perspective. It discusses definitions of the terminology of healing and health and their ethical and medical implications including their historical contexts. A separate section expands the theme of the cultural constructedness of healing by the concepts of traditional Chinese medicine and homeopathy. Modern medicine has a strong focus on acute care, which urgently needs to place greater emphasis on preventive medicine including the crucial importance of social factors on health and on the emergence of "public health". The point of view of Business Concepts, their potential and limitations are by no means neglected and the legal ramifications of genetic research and innovative medical strategies with regard to some of our most foundational notions are discussed.